Enhanced solar-radiation induced photocatalytic activity of surface-modified nanocrystalline anatase-titania - Priya, R.; Baiju, K. V.; Shukla, S.; Biju, S.; Reddy, M. L. P.; Patil, K. R.; Warrier, K. G. K. (Catalysis Letters, 2009)
Sol-gel derived pure nanocrystalline (similar to 20-30 nm) anatase-titania has been surface-modified by depositing silver(I) oxide and silver (predominantly the former) via UV-reduction process. The pure and surface-modified nanocrystalline anatase-titania have been characterized using different analytical techniques for determining the average nanocrystallite size, phase-contents, surface-chemistry, as well as the absorption and photoluminescence characteristics. It is demonstrated that, the latter exhibits an enhanced solar-radiation induced photocatalytic activity as compared to that of the former as a result of the absorption in the visible-region and enhanced photo-induced e(-)/h(+) life-time, both caused by the surface-deposition of silver(I) oxide and silver.
Keywords: Nanocrystalline; Photocatalysis; Silver; sol-gel; titania; UV-reduction